The Impact of Biofertilizers, Organic Fertilizers, and Foliar Application of Boron on Yield Characteristics of Maize (Zea mays L.) - Mohammed R. Ajeel; Mohammed M. Hamid Hamid; Ismail R. Al-Shahbani (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study took place under silty loam soil conditions at the Al-Musayyib project site (Babil Governorate, Iraq) from 15 July to 10 November 2024, to assess the interactive effects of biofertilizers, applied organic manure, and boron foliar application on yield attributes of maize (Zea mays L. Al-Maha). An experiment laid down in factorial arrangements in randomized complete block design (RCBD) consisted of three factors: an Azotobacter and Azospirillum seed inoculation (uninoculated, inoculated) and sheep manure in quantities of 0, 10, and 20 Mg ha⁻¹ and boron (boric acid) applied as a foliar treatment at levels of 0, 75, and 150 mg L⁻¹. Biofertilization in combination with high rates of organic manure and foliar spraying of boron gave great responses in the major yield components of dry matter yield, grains per cob, and total grain yield. The three-way interaction between the applied treatments achieved a significant contribution in synergy for all measured yield attributes. The results point towards the opportunity for integrated nutrient management to improve maize productivity under silty loam conditions as a feasible alternative to conventional fertilization approaches